PENGARUH MODEL PEMBELAJARAN TALKING STICK PADA MATERI HIMPUNAN TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS VII SMPS KATOLIKCHRISTO REGI - Imelda Gona Reda (Program Studi Pendidikan Matematika, 2020)
Students do learning activities by memorizing so that in learning mathematics critical thinking skills are still very low. One effort to solve this problem researchers used the Talking Stick learning model. The purpose of this study was to analyze the effect of the Talking Stick learning model on the critical thinking skills of grade VII Catholic Christo Regi Ende SMPS students. This type of research in this research is Causal Comperative research. Independent variable (X) talking stick and dependent variable (Y) critical thinking. Sample as many as 27 people. Data analysis using regression analysis with a significance level of 5%. The results showed that the residual assumption test results were normally distributed, there was no multicollinearity, no autocorrelation, and no heteroscedasticity. The significant level obtained from the results of the regression analysis is 0,000 <0.05. The conclusion drawn is rejecting H0 and accepting H1 means that there is an influence of the Talking Stick learning model on the critical thinking skills of students in class VII Catholic SMPS Christo Regi Ende.Thus it can be suggested that the school makes the talking stick model as an alternative to support students' critical thinking skills, teachers are expected to choose the right learning model and create a pleasant learning atmosphere. For students must have a critical attitude and courage to ask questions when experiencing difficulties.